Perception of the Sagas Of Icelanders in Modern Icelandic Crime Novels (Proceedings of Southern Federal University. Philology, 2019)
Olga A.Markelova (Moscow, Russian Federation)In modern Icelandic society the Old Icelandic literature is an important national topos, and using it as the material for crime stories is a well-chosen form for making this „great literary heritage“ closer to the reader. The origin of Icelandic crime stories has nothing in common with the Old Icelandic prose, but these genres have some „intersection points“.This paper deals with three crime novels: „The Uncertain Time of Death“ (Dauðans óvissi tími, 2004) by Thráinn Bertelsson and the two novels by Thórunn Erlu-Valdimarsdóttir: “Cold Is the Other´s Blood” (Kalt er annars blóð, 2007) and “The Lion Has May Ears” (Mörg eru ljóns eyru, 2010).„The Uncertain Time of Death“ uses the „Fóstrbræðra Saga“ (The Saga of the Sworn Brothers). The plot of the novel is based on the „viking“ concept; but what was considered valour in the Saga age, is regarded as a deviant behavour nowadays. The position of the saga heros in the modern soiety is miserable, and the main concepts of the viking age (e.g. feud) are subjected to criticism.In the novel “Cold Is the Other´s Blood” many persons correspond to the persons of “Njal´s Saga”, but the plot of the saga is not wholly re-created in the novel, there are only revealed the main events. The style of the novel is quite the opposite to the saga style. There are episodes in the novel which demonstrate, that the sagas still are important for modern Icelanders, while some other national symbols may already cease to „work“.“The Lion Has May Ears” reproduces the plot and the main persons of the „Laxdæla Saga“ and has some non-saga plot lines along with it. The fate of Guðrún Ósvifsdóttir receives an unexpected addition in the novel. (Normally, in modern Icelandic prose the fortune of persons of the saga origin does not change).For the authors of the crime novels there is more important not to follow the ancient texts thoroughly, but to create a reminder of those texts, to manifestate their connection to the Old Icelandic literature. The symbol, important for the particular national culture, is made „alive“ and gets „closer“ to the reader without losing ist symbolic nature.Key words: modern Icelandic literature, the sagas of Icelanders, Icelandic crime novel, perception, intertextuality.DOI 10.23683/1995-0640-2019-1-156-166